Combining adsorption and coagulation for the treatment of azo and anthraquinone dyes from aqueous solution - Karadag, Dogan; Tok, Sema; Akgul, Eda; Ulucan, Kubra; Evden, Hulya; Kaya, Mehmet A. (AMER CHEMICAL SOC, 2006)
The combined process of coagulation and adsorption was studied for the treatment of reactive dye wastewaters. Ferric chloride and organozeolite modified with CTAB were chosen as the coagulant and adsorbent, respectively. Reactive dyes, namely, Reactive Blue 4 (RB4) and Reactive Yellow (RY), were used as representatives of anthraquinone and azo textile dyes. A series of jar-test and batch experiments were conducted to determine the optimum conditions. According to individual dye removal efficiencies, coagulation is the main treatment process of the combined process, and RY has better performance than RB4. Coagulation followed by adsorption was found to be very effective for color removal with more than 99.50% and for COD removal with more than 97.25%.
Keywords: TEXTILE WASTE-WATER; REACTIVE-DYE; NANOFILTRATION MEMBRANES; OZONATION; EFFLUENTS; REMOVAL; Engineering